United Nations handbook - 2015-16 - (New Zealand. Ministry of Foreign Affairs and Trade / Manatu Aorere WellingtonNZ, 2015)
Presents information on the six principal UN organs established by the UN Charter: the General Assembly, Security Council, Economic and Social Council, Trusteeship Council, International Court of Justice and the Secretariat. Contains information about subsidiary organs established in accordance with the Charter, related UN organs and programmes, specialised agencies and autonomous bodies related to the UN, and various ad hoc organs and programmes.
Documentation Centre has: 2015-61; 2017-18